Seasonal variations in body composition, maximal oxygen uptake, and gas exchange threshold in cross-country skiers - Polat,Metin; Korkmaz EryÄ±lmaz,Selcen; Aydogan,Sami (Open Access Journal of Sports Medicine, 2018)
Metin Polat,1 Selcen Korkmaz EryÄ±lmaz,2 Sami AydoÄŸan3 1School of Physical Education and Sports, Erciyes University, Kayseri, Turkey; 2School of Physical Education and Sports, Cukurova University, Adana, Turkey; 3Department of Physiology, Faculty of Medicine, Erciyes University, Kayseri, Turkey Introduction: In order to ensure that athletes achieve their highest performance levels during competitive seasons, monitoring their long-term performance data is crucial for understanding the impact of ongoing training programs and evaluating training strategies. The present study was thus designed to investigate the variations in body composition, maximal oxygen uptake (VO2max), and gas exchange threshold values of cross-country skiers across training phases throughout a season. Materials and methods: In total, 15 athletes who participate in international cross-country ski competitions voluntarily took part in this study. The athletes underwent incremental treadmill running tests at 3 different time points over a period of 1 year. The first measurements were obtained in July, during the first preparation period; the second measurements were obtained in October, during the second preparation period; and the third measurements were obtained in February, during the competition period. Body weight, body mass index (BMI), body fat (%), as well as VO2max values and gas exchange threshold, measured using V-slope method during the incremental running tests, were assessed at all 3 time points. The collected data were analyzed using SPSS 20 package software. Significant differences between the measurements were assessed using Friedman’s twoway variance analysis with a post hoc option. Results: The athletes’ body weights and BMI measurements at the third point were significantly lower compared with the results of the second measurement (p<0.001). Moreover, the incremental running test time was significantly higher at the third measurement, compared with both the first (p<0.05) and the second (p<0.01) measurements. ...